Leukocyte telomere length and mycophenolate therapy in chronic hypersensitivity pneumonitis. Issue 3 (4th March 2021) - Adegunsoye, Ayodeji; Morisset, Julie; Newton, Chad A.; Oldham, Justin M.; Vittinghoff, Eric; Linderholm, Angela L.; Strek, Mary E.; Noth, Imre; Garcia, Christine Kim; Wolters, Paul J.; Ley, Brett
Recent prospective clinical trials have shown antifibrotic therapies slow lung function decline in patients with idiopathic pulmonary fibrosis (IPF) [1, 2] and progressive fibrosing interstitial lung disease (ILD). Similar findings were demonstrated in scleroderma-associated ILD [3], despite use of the immunosuppressive therapy mycophenolate mofetil (MMF). Prospective data for the treatment of other forms of ILD, such as chronic hypersensitivity pneumonitis (CHP) are lacking. Our groups previously reported that the treatment of CHP with MMF was associated with a decreased incidence of adverse events, a reduction in prednisone dose, and improved lung function when compared to prednisone alone [4, 5], but prospective studies are needed to confirm these findings. Patients with chronic hypersensitivity pneumonitis and telomere lengths above the first quartile may have improved survival with mycophenolate therapy. https://bit.ly/3maRXih